Epidemiological and clinical variables’ behavior in patients with stroke of Villa Clara - Bettsy Bell Bosch Rodriguez; Arlet López Quintanilla; Mercedes Bordón Hernández; Marbelys Guevara Rodríguez; Eldis Daniel Rodríguez León; Amalia Inés Luna Capote (Medisur, 2023)
Background: cerebrovascular disease represents the most common health problem related to neurological care, it is important to study it in different contexts and from different approaches. Objective: to describe epidemiological and clinical variables’ behavior in patients admitted for stroke. Methods: descriptive and cross-sectional study, carried out in Arnaldo Milián Castro Hospital’s Neurology service from Villa Clara, Cuba, which included all patients with a clinical diagnosis of cardioembolic or atherothrombotic stroke, admitted to the ward during 2019. The information was obtained from the medical records stored in the Hospital Archive; and it was processed in the statistical package SPSS. v. 21. A descriptive statistical analysis was applied, in a frequency distribution. Results: female patients predominated (51.6%). There was a higher incidence in men older than 79 years (47.7%), and in women older than 70 (86.0%). In 67.3% the cardioembolic cause was demonstrated. Arterial hypertension was the main associated risk factor (83.6%). The motor defect was observed as the most frequent clinical finding on admission (96.7%). Hemorrhagic transformation of the infarct and nosocomial bronchopneumonia were identified as the main neurological and non-neurological complications, respectively. Patients discharged alive prevailed (68.6%). Conclusions: ischemic strokes are more frequent in elderly patients; early identification and timely management of the established disease can largely prevent the appearance of complications, and consequently death.